Carfilzomib, dexamethasone, and daratumumab versus carfilzomib and dexamethasone for patients with relapsed or refractory multiple myeloma (CANDOR): results from a randomised, multicentre, open-label, phase 3 study. Issue 10245 (18th July 2020) - Dimopoulos, Meletios; Quach, Hang; Mateos, Maria-Victoria; Landgren, Ola; Leleu, Xavier; Siegel, David; Weisel, Katja; Yang, Hui; Klippel, Zandra; Zahlten-Kumeli, Anita; Usmani, Saad Z
Summary: Background: Lenalidomide and bortezomib frontline exposure has raised a growing need for novel treatments for patients with relapsed or refractory multiple myeloma. Carfilzomib in combination with daratumumab has shown substantial efficacy with tolerable safety in relapsed or refractory multiple myeloma in a phase 1 study. In this study, we aimed to compare the efficacy and safety of carfilzomib, dexamethasone, and daratumumab versus carfilzomib and dexamethasone in patients with relapsed or refractory multiple myeloma. Methods: In this randomised, multicentre, open-label, phase 3 study, 466 patients recruited from 102 sites across North America, Europe, Australia, and Asia with relapsed or refractory multiple myeloma were randomly assigned 2:1 to carfilzomib, dexamethasone, and daratumumab (KdD) or carfilzomib and dexamethasone (Kd). All patients received twice per week carfilzomib at 56 mg/m 2 (20 mg/m 2 ; days 1 and 2 during cycle 1). Daratumumab (8 mg/kg) was administered intravenously on days 1 and 2 of cycle 1 and at 16 mg/kg weekly for the remaining doses of the first two cycles, then every 2 weeks for four cycles (cycles 3–6), and every 4 weeks thereafter. Patients received 40 mg dexamethasone weekly (20 mg for patients ≥75 years old starting on the second week). The primary endpoint was progression-free survival assessed by intention to treat. Adverse events were assessed in the safety population. This trial (NCT03158688 ) is registered with ClinicalTrials.gov, and is active but not recruiting. Findings: Between June 13, 2017, and June 25, 2018, 466 patients of 569 assessed for eligibility were enrolled. After median follow-up of approximately 17 months, median progression-free survival was not reached in the KdD group versus 15·8 months in the Kd group (hazard ratio 0·63; 95% CI 0·46–0·85; p=0·0027). Median treatment duration was longer in the KdD versus the Kd group (70·1 vs 40·3 weeks). Grade 3 or higher adverse events were reported in 253 (82%) patients in the KdD group and 113 (74%) patients in the Kd group. The frequency of adverse events leading to treatment discontinuation was similar in both groups (KdD, 69 [22%]; Kd, 38 [25%]). Interpretation: KdD significantly prolonged progression-free survival versus Kd in patients with relapsed or refractory multiple myeloma and was associated with a favourable benefit–risk profile. Funding: Amgen.